2004
DOI: 10.1161/01.cir.0000149840.46523.fc
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Tracking of Stem Cells for Clinical Trials in Cardiovascular Disease

Abstract: Abstract-Various stem cells hold promise for the treatment of human cardiovascular disease. Regardless of stem cell origin, future clinical trials will require that the location and number of such cells be tracked in vivo, over long periods of time. The problem of tracking small numbers of cells in the body is a difficult one, and an optimal solution does not yet exist. We review the many contrast agents and detectors that have been proposed for stem cell tracking during clinical trials, define the characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
213
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(218 citation statements)
references
References 50 publications
0
213
0
5
Order By: Relevance
“…11,12 The number of human studies on transfer of stem cells and subsequent tracing of these cells is still limited, 4,13,14 as tracking of stem cells in vivo is still difficult in humans. 15,16 Recent studies in patients after HTX or BMT have shown an influx, repopulation and differentiation of BMderived cells in the heart, originating from the cardiac recipient or the BMT donor, respectively. However, the reported number of invading stem cells that, evidently, differentiate into cardiomyocytes varied considerably between the various experimental and human studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 The number of human studies on transfer of stem cells and subsequent tracing of these cells is still limited, 4,13,14 as tracking of stem cells in vivo is still difficult in humans. 15,16 Recent studies in patients after HTX or BMT have shown an influx, repopulation and differentiation of BMderived cells in the heart, originating from the cardiac recipient or the BMT donor, respectively. However, the reported number of invading stem cells that, evidently, differentiate into cardiomyocytes varied considerably between the various experimental and human studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reported number of invading stem cells that, evidently, differentiate into cardiomyocytes varied considerably between the various experimental and human studies. 9,10,[14][15][16][17][18][19][20] This heterogeneity is most likely the result of an overestimation of host-derived cardiomyocytes, due to the presence of large number of infiltrating host-derived inflammatory cells and/or to the application of a variety of different detection techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in the isolation of stem cells along with improved understanding of their functions has extended the use of stem cells in cardiovascular and neurologic diseases [1]. The development of stem cell-based therapies requires a quantitative and qualitative assessment of initial stem cell distribution to target organs (homing) as well as engraftment and in situ differentiation.…”
mentioning
confidence: 99%
“…The development of stem cell-based therapies requires a quantitative and qualitative assessment of initial stem cell distribution to target organs (homing) as well as engraftment and in situ differentiation. Several imaging techniques are proposed to track stem cells in vivo within individual organs over long periods of time [1]. However, tracking a small number of cells in the body is a difficult task and the ideal technique has not yet been delineated [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation